Maxim Analysis of Maxim Usage in Marital Conversations: A Study of Batak Couple Dynamics in the Movie 'Ngeri-Ngeri Sedap’ - Syafrayani, Putri Rizki; Ayunda, Riska (English Teaching and Linguistics Journal (ETLiJ), 2025)
This study analyzed the application and violation of Grice's maxims in marital conversations between Batak couples as depicted in the film "Ngeri-Ngeri Sedap." Employing a qualitative descriptive approach, the research focused on dialogues between the central characters, Bapak Domu and Mamak Domu, to investigate how cultural norms and gender roles shape communication dynamics within Batak society. The findings indicated that the maxim of Quantity was the most frequently adhered to, suggesting that the couple generally provided an appropriate amount of information. However, it was also the most commonly violated maxim, often due to emotional tensions or strategic interactions. The analysis revealed distinct communication patterns, with male speakers more likely to withhold information while female speakers adhered more closely to conversational norms, particularly in emotionally charged situations. This study contributes to understanding how cultural values influence marital communication and highlights the significance of maxim violations in navigating relational complexities. By exploring the interplay between culture, gender, and pragmatics, the research offers valuable insights into the evolving nature of marital dynamics in contemporary Batak society.